Comparison of Two Apheresis Systems of COBE and Optia for Autologous Peripheral Blood Stem Cell Collection - Lee, Se-Na; Sohn, Ji Yeon; Kong, Jung Hee; Eom, Hyeon Seok; Lee, Hyewon; Kong, Sun-Young (Annals of laboratory medicine, 2017)
Peripheral blood stem cell (PBSC) transplantation following myeloablative therapy is a mainstay of treatment for various types of malignancies. This study aimed to evaluate the differences between the Optia MNC and COBE Spectra MNC systems (Terumo BCT, Japan) according to apheresis procedures and the parameters of apheresis, products, and collection. The clinical data of 74 patients who underwent autologous PBSC collection from July 2012 to July 2015 were reviewed retrospectively. The patients comprised 48 (65%) men and 26 (35%) women with a median age of 56 yr (range, 23-66 yr). Of 216 procedures, 111 (51%) and 105 (49%) were processed by using COBE and Optia MNC, respectively. PBSC collection rates, throughput, numbers of stem cells retrieved, collection efficacy, and platelet loss were compared. There were no significant differences in the median CD34+ cell counts of collected products (0.61×10⁸ vs 0.94×10⁸), CD34 collection efficiency (43.5% vs 42.1%), and loss of platelets (40.1% vs 44.7%). The Spectra Optia MNC apheresis system was comparable to the COBE Spectra system in collecting autologous CD34+ hematopoietic stem cells and retention of platelets.